Think Aloud Analysis of Probability Word Problems among College Students - YUSUF, MARDIANA BT; Abdul Rahim, Suzieleeze Serene bt (Proceedings of the International Conference on Education, 2019)
This study explores the strategies used in solving probability word problems by a college student. Problem solving with various ways of solutions was a bit complicated for students in need to choose the best strategy to solve them. Thinking aloud used as an analysis tool to evaluate the influence thought and behaviour of the participants in the study during solving seven tasks. Three participants were chosen as a preliminary of a case study. An in-depth semi-structured interview was conducted together with the think-aloud analysis to gain rich and thick descriptions from the participants. Protocols were coded and analyzed to determine what strategies they used and why they choose those strategies to solve the problems. Results indicated that participants loved to use visual representations as strategies in solving probability problems such as basic diagrams and sketches without knowing the accuracy of its effect.